Analisis Pengaruh Indeks Pembangunan Manusia, Penyerapan Tenaga Kerja dan Pertumbuhan Ekonomi terhadap Tingkat Kemiskinan di Jawa Timur - Adelia Wahyu Apriliana; Wiwin Priana Primandhana (Syntax Corporation, 2023)
Development is one way to bring about change, where change itself is one way to achieve a goal. This study aims to determine the relationship between HDI, Labor Absorption and Economic Growth in East Java for the 2007-2022 period. This study uses a quantitative approach with secondary data. This study uses multiple linear regression analysis using the SPSS application. From the results of the analysis it was found that HDI and Labor Absorption had a significant negative effect on the poverty rate in East Java. Meanwhile, economic growth has no significant effect on the level of poverty in East Java. From this research it is hoped that the government can further improve the quality of human development and employment so that economic growth can be significant.